153k views
5 votes
What is the solution to the system? x+y-z=0
3x-y+z=4
5x+z=7

What is the solution to the system? x+y-z=0 3x-y+z=4 5x+z=7-example-1
User Ohad
by
5.3k points

1 Answer

4 votes

Answer:

D. (x, y, z) = (1, 1, 2). That is:


\left\{\begin{aligned}&x = 1\\ & y = 1 \\&z = 2\end{aligned}\right..

Explanation:

Step One: Make sure that the first coefficient of the first row is 1. In this case, the coefficient of
x in the first row is already 1.

Step Two: Using row 1, eliminate the first unknown of row 1
x in the rest of the rows.
For example, to eliminate
x from row 2, multiply row 1 by the opposite of the coefficient of
x in row 2 and add that multiple to row 2. The coefficient of
x in row 2 is
3. Thus, multiply row 1 by
-3 to get its multiple:


-3x - 3y + 3z = 0.

Add this multiple to row 2 to eliminate
x in that row:


\begin{array}{lrrrcr}&-3x &-3y&+3z& =&0 \\ + & 3x& -y& +z& =& 4\\\cline{1-6}\\[-1.0em]\implies&&-4y &+ 4z&=&4\end{array}.

Similarly, for the third row, multiply row 1 by
-5 to get:


-5x - 5y + 5z = 0.

Do not replace the initial row 1 with this multiple.

Add that multiple to row 3 to get:


\begin{array}{lrrrcr}&-5x &-5y&+5z& =&0 \\ + & 5x& & +z& =& 7\\\cline{1-6}\\[-1.0em]\implies&&-5y &+6z&=&7\end{array}.

After applying step one and two to all three rows, the system now resembles the following:


\left\{\begin{array}{rrrcr}x& + y & -z& = &0\\&-4y &+4z&=&4\\ &-5y &+6z&=&7\end{array}\right..

Ignore the first row and apply step one and two to the second and third row of this new system.


\left\{\begin{array}{rrcr}-4y &+4z&=&4\\ -5y &+6z&=&7\end{array}\right..

Step One: Make sure that the first coefficient of the first row is 1.

Multiply the first row by the opposite reciprocal of its first coefficient.


\displaystyle (-(1)/(4))\cdot (-4y) + (-(1)/(4))\cdot 4z = (-(1)/(4))* 4.

Row 1 is now
y - z = -1.

Step Two: Using row 1, eliminate the first unknown of row 1
y in the rest of the rows.

The coefficient of
y in row 2 is currently
-5. Multiply row 1 by
5 to get:


5y - 5z = -5.

Do not replace the initial row 1 with this multiple.

Add this multiple to row 2:


\begin{array}{lrrcr}&-5y&+6z& =&7 \\ + & 5y& -5z& =& -5\\\cline{1-5}\\[-1.0em]\implies&&z &= &2\end{array}.

The system is now:


\left\{\begin{array}{rrcr}y & - z&=&-1\\& z &=&2\end{array}\right..

Include the row that was previously ignored:


\left\{\begin{array}{rrrcr}x& + y & -z& = &0\\&y &-z&=&-1 \\ & &z&=&2\end{array}\right..

This system is now in a staircase form called Row-Echelon Form. The length of the rows decreases from the top to the bottom. The first coefficient in each row is all
1. Find the value of each unknown by solving the row on the bottom and substituting back into previous rows.

From the third row:
z = 2.

Substitute back into row 2:


y -2 = -1.


y = 1.

Substitute
y = 1 and
z = 2 to row 1:


x + 1 - 2 = 0.


x = 1.

In other words,


\left\{\begin{aligned}&x = 1\\ & y = 1 \\&z = 2\end{aligned}\right..

User Bato
by
5.6k points